Ethnic dominance and exclusion: Unpacking cross-national data - Andrea Vaccaro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
It is widely accepted that the distribution of power between ethnic groups within a country plays a key role in major social, political, and economic outcomes. Researchers working on the topic have various measures of ethnic dominance and exclusion, and other closely related aspects such as ethnic fractionalization, polarization, and heterogeneity, available to them. These measures are, however, often used without sufficient critical reflection and their empirical differences are not entirely understood. The literature does not provide too much guidance either. In fact, efforts to comparatively evaluate data on how power is distributed between ethnic groups are in short supply. To address this gap in the literature, the study at hand provides a comprehensive descriptive analysis of publicly available common cross-national country-level measures on ethnic dominance and exclusion. The findings of this study suggest that Varieties of Democracy's Exclusion by Social Group and Ethnic Power Relations' Ethnic Exclusion are more alike than the other measures under scrutiny, yet in general the empirical differences among common measures of ethnic dominance and exclusion are substantial. Scholars should thus reject an 'any measure will do' approach when choosing among competing measures.
Keywords: D70; J15; N30; 330; ethnic dominance; ethnic exclusion; ethnicity; data; indicators; measurement